Criptografia: A Teoria e a prática em sala de aula - Reis, Matheus Alves Machado (2023)
Cryptographic methods play a crucial role in protecting the privacy and security of digital communications, ensuring that sensitive information remains confidential in an increasingly connected world. In order to obtain a better understanding of some of these methods, the objectives of this work are to study the cryptographic methods Caesar Cipher and RSA Cryptography, in addition to presenting a proposal and applying an activity on Caesar Cipher in the classroom.